The Central Cemetery of Cúcuta. In-memoriam, recognitions and merits - Mena Uscategui, Fabián Alfredo; Abadía Martínez, Juan Francisco; Mosquera Téllez, Jemay (2024)
The main objective of the work is to recognize, value, recover and make visible the material and intangible cultural heritage of Cúcuta, represented in the city’s Central Cemetery. The hermeneutic methodological structure, with a mixed approach, documentary in character complemented by field work, deductive and inductive approaches, quantitative and qualitative, enabled the generation of theoretical bases for cultural management and the elaboration of contextual diagnosis with their respective general historical background of the city, and the formal, aesthetic and symbolic graphic consolidation of the works present in the Cemetery, as well as findings that highlight its historical, urban and cultural value. The results contribute to the appropriation of knowledge associated with the rediscovery of the funerary heritage of Cúcuta, historical-symbolic recognition of the socio-cultural, urbanistic, architectural and artistic manifestations of the Central Cemetery of the city as an archive and individual and collective cultural memory of its inhabitants. They can also serve as support to strengthen the role of the cemetery in cultural management and regional development.
Keywords: Cultural management; Memory; Funerary heritage; Artistic works; Safeguarding